Presentations and complications of diabetes patients presenting to diabetic clinic of Eastern Nepal - Nabin Kumar Singh (Journal of College of Medical Sciences-Nepal, 2014)
Objective Diabetes mellitus leads to damage, dysfunction and failure of various organs especially eyes, kidneys, nerves and heart. The latency of occurence of hyperglycemia and diagnosis may be of long duration. This study was aimed to find out the mode of presetation of diabetes mellitus in diabetic patients attending out patients clinic of B P Koirala Institute of Health Sciences. Associated complications and comorbid condition present at the time of presenation were also studied. Methods The diabetic patients attending the Diabetic Out Patient Clinic of B P Koirala Institute of Health Sciences during June 2006 to June 2007 were included in this study.The patients details were collected from the predefined Proforma for diabetes patient from the database. This included demographic data, biochemical parameters and diabetic complications. For the purpose of study a total of 775 patients were randomly selected.The Data collected were entered and analysed using excel and SPSS(version 11.5) Results Out of 775 cases 436 (56.3%) were male and 339(43.7%) were female. Majority of patients 81.55% (n=632) had osmotic sympmtoms or symptoms related to complication of diabetes at the time of presentation to the clinic. Asymptomatic patient constituted 18.45% (n=143). The most common presenting complaints were polyuria (44.58%), followed by polydypsia (39.62%) and polyphagia (24.88%). About 54.97% (n=426) had symptoms of complications related to diabetes. Among them most common complication was neurological (39.67%), followed by renal (10.8%) metabolic (4.93%), cardiac(4.46%), autonomic neuropathy (4.93%) and peripheral vascular disease (3.99%). Conclusion Majority of the patients presenting in our OPD had osmotic symptoms or symptoms related to complication of diabetes. Access to diabetes care and lack of awareness of the disease and its complication might had contributed to this. Community awareness, program for early detection and managemnet may help proper diabetes care and prevention of complications.    Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 25-30 DOI: http://dx.doi.org/10.3126/jcmsn.v9i3.10216